Low social status decreases the neural salience of unfairness - Hu, Jie; Cao, Yuan; Blue, Philip R.; Zhou, Xiaolin (Frontiers in Behavioral Neuroscience, 2014)
Social hierarchy exists in almost all social species and affects everything from resource allocation to the development of intelligence. Previous studies showed that status within a social hierarchy influences the perceived fairness of income allocation. However, the effect of one’s social status on economic decisions is far from clear, as are the neural processes underlying these decisions. In this study, we dynamically manipulated participants’ social status and analyzed their behavior as recipients in the ultimatum game, during which event-related potentials (ERPs) were recorded. Behavioral results showed that acceptance rates for offers increased with the fairness level of offers. Importantly, participants were less likely to accept unfair offers when they were endowed with high status than with low status. In addition, cues indicating low status elicited a more positive P2 than cues indicating high status in an earlier time window (170 – 240 ms), and cues indicating high status elicited a more negative N400 than did cues indicating low status in a later time window (350 – 520 ms). During the actual reception of offers, the late positivity potential (LPP, 400 – 700 ms) for unfair offers was more positive in the high status condition than in the low status condition, suggesting a decreased arousal for unfair offers during low status. These findings suggest a strong role of social status in modulating individual behavioral and neural responses to fairness.